English English - Aliyah, Tuti; Yuliyanto, Aan; Farikhin, Iing; Amanaturrakhmah, Isna; Tasrini; Yasin, Mustofa (International Conference on Elementary Education, 2024)
Creative thinking is a high-level ability to find, create, and compile ideas or ideas for solving problems. There are five aspects: fluent thinking, flexible thinking, Originality, Elaboration, and evaluation. In this literature review, we will discuss the impact of implementing wordwall learning media to improve the creative thinking abilities of grade 3 elementary school students in science learning. Wordwall learning media has been proven to increase students' interest, creative thinking, and motivation in the learning process and bring students abreast of current developments. This wordwall learning media can be an effective alternative for presenting learning material to students, especially for displaying images and interactive learning activities.